2007
DOI: 10.1161/atvbaha.107.143479
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Platelets by Misfolded Proteins

Abstract: Objective-Protein misfolding diseases result from the deposition of insoluble protein aggregates that often contain fibrils called amyloid. Amyloids are found in Alzheimer disease, atherosclerosis, diabetes mellitus, and systemic amyloidosis, which are diseases where platelet activation might be implicated. Methods and Results-We induced amyloid properties in 6 unrelated proteins and found that all induced platelet aggregation in contrast to fresh controls. Amyloid-induced platelet aggregation was independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 37 publications
(43 reference statements)
2
60
1
Order By: Relevance
“…This assumption is consisted with the results from other groups who have already shown that AGE-BSA induces PLT reactivity [15,18] while some glycated structures like CML (Nε-(carboxymethyl)lysine) and pentosidine have no effect on these cells [16]. They have discussed their observation based on the presence of some essential epitopes in AGE-BSA.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…This assumption is consisted with the results from other groups who have already shown that AGE-BSA induces PLT reactivity [15,18] while some glycated structures like CML (Nε-(carboxymethyl)lysine) and pentosidine have no effect on these cells [16]. They have discussed their observation based on the presence of some essential epitopes in AGE-BSA.…”
Section: Discussionmentioning
confidence: 58%
“…This PLT malfunction has been attributed in part to hyperglycemia and glycation reactions that might aggravate with a higher rate in hyperglycemia conditions [24]. Aforementioned reactions affect PLT function by different mechanisms [15]. Several studies have revealed that an increase in PLT reactivity upon treatment with AGE proteins; though their influences vary remarkably [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations